Time series of concentration, best cross-correlation and shift of two stations at the Starzach site. - Yann Georg Büchau (22683667) (2025)
Time series of station 6 and station 26 (top) are cross-correlated in a 10 min rolling window to determine the shift between them (bottom) from the highest cross-correlation value (center). In the lowest panel, the y-axis has a symmetric logarithmic scale, but the region −10 to 10 s is scaled linearly. See Fig 4 for a zoomed view.